Natural killer cell infusion for cytomegalovirus infection in pediatric patients with Wiskott-Aldrich syndrome following cord blood transplantation: A case report and literature review - Yue, Yongwei; Meng, Lijun; Ling, Jing; Fan, Liyan; Zhang, Yanlei; Hu, Yixin; Chang, Alex H.; Hu, Shaoyan (Frontiers in Medicine, 2022)
NK cells have important functions in resisting cytomegalovirus infection, as they proliferate after virus’ infection and have certain infection’ memory. Here, we report infusion of haploid donor-derived natural killer cells to treat two pediatric patients with Wiskott–Aldrich syndrome (WAS) who were infected with cytomegalovirus post-cord blood transplantation (CBT), which successfully cleared the viral infection in both patients.